Comparison of methane, nitrous oxide fluxes and CO2 respiration rates from a Mediterranean cork oak ecosystem and improved pasture - Shvaleva, Alla; e Silva, Filipe; Costa, Joaquim Miguel; Correia, Alexandra; Anderson, Margaret; Lobo-do-Vale, Raquel; Fangueiro, David; Bicho, Catarina; Pereira, Joo Santos; Chaves, Maria Manuela; Skiba, Ute; Cruz, Cristina (PLANT AND SOIL, 2014)
During the recent decades, cork oak (Q. suber) mortality has been increasing in Mediterranean oak woodland endangering the economical and environmental sustainability of the ``montado{''} ecosystem. This fact in combination with climate change and conversion of forestland to pasture may significantly affect the soil-atmosphere greenhouse gases (GHGs) exchange. Our study evaluates the impact of oak trees as compared to pasture on net ecosystem GHG (CH4, N2O, and CO2) exchange as well as the main environmental factors influencing this exchange. We used field chamber measurements for the collection of GHGs under three different conditions: 1) open area (OA), 2) under tree canopy area (UC) and 3) improved pasture (IP). Experiments were done under typical Mediterranean climate at central Portugal in 2010 and 2011. The UC had higher nitrification potential, soil C/N ratio, electrical conductivity, litter input and soil organic matter (SOM) than OA and IP. SOM positively correlated with soil CH4 and N2O fluxes but not with soil CO2 respiration rates. Soil water content (SWC) drives both CH4 and N2O fluxes. Under certain conditions, when SWC reached a threshold (7 % for CH4 and 3 % for N2O) the result was net uptake and that net uptake increased with SWC. This was the case for the UC and OA. Conversely, for the IP soil water content above 4 % promoted net CH4 release. Our results show that cork oak influences soil properties and consequently GHGs fluxes. In the UC the input of litter for SOM together with soil moisture, favoured microbiological activity and related GHGs fluxes. Soil temperature is a secondary factor in the studied conditions. Our results also emphasized the potential impact posed by decreased cork oak tree density in the functioning of the ``montado{''} ecosystem.
Keywords: evergreen oak; Greenhouse gases; litter; Mediterranean; organic matter; Root density

Mycocoenologic study of the macrofungi on the forest of Jbel elbir (Aïn Draham, Jendouba, Tunisia) - Ben Hassine Ben Ali, Mourad; Aschi-Smiti, Samira; Ben, Mourad; Ben, Hassine (African Journal of Ecology, 2013)
Macrofungi have important functions in forest ecosystems. It is essential to have information about these species to ensure proper management of such ecosystems. Due to the importance of forestry in Tunisia and the lack of information on fungal communities, this study was conducted in North Western of Tunisia. The objective was to enumerate macrofungal diversity in relation to various environmental factors. In total, 158 fruiting bodies were collected and 60 species were identified. Among them, 39 species are mycorrhizal. A fruiting body is the first visible appearance of the spore-bearing surface until its disintegration. More fruiting bodies were found on the eastern slopes than on the western slopes. This reflects the distribution of tree species and soil type. Almost all fungal species were collected from soils of moderate acidity (pH 4–pH 5), 5 species from soils with low acidity (pH 5–pH 6.8), and only 3 species from soils with high acidity (pH < 4). The majority of fruiting bodies occurred in soils with a percentage of organic matter ranging from 1 to 5 and a phosphorus content ranging from 15.1 to 20 ppm.
Keywords: Altitude; exposure; Macrofungi; mycocoenology; organic matter; pH; Tunisia

Spatial pattern of soil compaction: Trees’ footprint on soil physical properties - Alameda, David; Villar, Rafael; Iriondo, José M. (Forest Ecology and Management, 2012)
Soil compaction, a determinant of forest regeneration and ecosystem functioning (e.g., biomass production), can show an aggregated spatial pattern which can be shaped by the effect of tree canopy. This work studies the inﬂuence of tree canopy type (Quercus ilex subsp. ballota, and Pinus pinaster) on the spatial distribution of variables related to soil compaction in a Mediterranean forest in southern Spain. The spatial structure of this plant-soil interaction was analyzed using the spatial analysis by distance indices methodology (SADIE). Our results showed that variables related to soil compaction, such as bulk density, penetration resistance, water content and organic matter, showed an aggregated spatial pattern which was associated to the species’ tree canopy and presence of open sites. Thus, high organic matter content and low bulk density were found under the Quercus canopy, whereas the contrary was observed under the Pinus canopy. Open sites showed similar soil properties to those than under the Pinus canopy. Soil compaction pattern and tree canopy had a clear effect on herbaceous production. In two consecutive years (2007 and 2008), herbaceous production was higher under the Quercus canopy than under the Pinus canopy. Mean values of herbaceous production in open sites were similar to those under the Quercus canopy, and no spatial association was found between open sites and herbaceous production. Structural equation modeling (SEM) was used to describe the causal relationships between tree canopy types, soil compaction related variables and herbaceous production. Results showed that tree canopy affects soil compaction variables and its effects on herbaceous production are mainly produced by a positive effect of organic matter (at 2–7 cm depth) and a negative effect of penetration resistance (at 9–14 cm depth). Therefore, forest management should consider that the replacement of one species for another or changes in tree density are likely to have important consequences in soil compaction and ecosystem functioning.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Bulk density; Herbaceous production; organic matter; Penetration resistance; Pinus pinaster; Quercus ilex

Materia orgánica de suelos bajo encinas. Mineralización de carbono y nitrógeno - Gonzalez Parra, J; Candás Villar, M A (Forest Systems, 2008)
Soil characteristics under evergreen oaks forest (Quercus rotundifolia Lam.) located at the East of Segovia were studied. The soils were formed from gneis and limestone. The whole soil was 0-20 cm depth. The soils were classified as mollic Leptosols, eutric Cambisols and calcaric Cambisols. Horizons sequences were the following: O, Ah1, Ah2, C and O, Ah1, Ah2, BC. Organic horizons (3-0 cm depth) were formed by the not-yet decomposed organic remains from evergreen oaks. Mean organic matter content was 25%. The C:N ratio was high and free organic carbon was near 90% of the total carbon, which correspond with a low degree of humification. Soil texture was loamy sand and sandy loam. Soils on limestone present the highest clay fraction contents. The bases saturation degree was high, being Ca 2+ the fundamental cation of exchange complex. Organic matter content and C:N ratio were lower in organic minerals horizons than in organic horizons. Humification degree was 60% with a predominance of HAs over FAs. The polimerization of humic substances makes possible the formation of humus «moder». Carbon mineralization to the total C was ten times higher than nitrogen mineralization in upper horizons. In all horizons the nitrification was higher than N mineralization. Carbon mineralization was lower and N mineralization was higher in deeper horizons compearing with upper horizons.
Keywords: mineralization; nitrogen; organic matter; Quercus rotundifolia; soils

USING A GIS FOR SUSTAINABLE USE AND MANAGEMENT OF AN IRRIGATION AREA IN THE SPANISH - PORTUGUESE BORDER THREATENED BY DESERTIFICATION - Muñoz, A (Desertification in the Mediterranean Region a Security Issue, 2006)
Inappropriate management of agricultural irrigated land, using excessive amounts of production factors – pesticides and fertilizers in particular – can lead to rapid and irreversible soil degradation and the corresponding decrease in production capacity. The method presented here, applicable to the entire Mediterranean region, was designed to support the sustainable management of a 12540 ha irrigated area located in the Spanish- Portuguese border, with special emphasis on the prevention of desertification. This specific tool, incorporates a data collection from 1428 georeferenced points and respective topsoil samples, describing soil type, depth, slope, drainage, pH, organic matter content, electrical conductivity, exchangeable sodium content, and available phosphorus and potassium. Parameterized maps were prepared for all these soil properties using Geographic Information System (GIS) software to store, manage, analyze, and display the georeferenced information. Predictive maps for organic amendments need were elaborated for use in the sustainable and integrated land management of the area. The higher risk zones were identified on the basis of their soil depth, slope, drainage, organic matter, electrical conductivity, and sodium saturation percentage.
Keywords: Caia Irrigation Perimeter; desertification; management (voyant); organic matter; soil properties

Soil microbial activity as a biomarker of degradation and remediation processes - Pascual, J.a; García, C; Hernández, T; Moreno, J L; Ros, M (Soil Biology and Biochemistry, 2000)
Several organic matter fractions together with biological and biochemical parameters were measured in a range of intensively farmed soils in SE Spanish Mediterranean region, which had been abandoned (i.e. not used in agriculture) for different periods of time. These soils were compared with adjacent natural soils that had never been used for agriculture. There was a general decline of total organic carbon (TOC), extractable humic substances, water-soluble carbon (WSC) and carbohydrates, microbial biomass and respiration with the time elapsed since abandonment. There was also a decline in plant cover in the abandoned soils. When a degraded soil was amended with municipal solid waste at rates of 6.5 and 26 kg m 22 as a potential means of remediation, TOC, humic substances, WSC, microbial biomass and respiration rates signi®cantly increased but only at the higher rate of amendment. Plant cover was signi®cantly enhanced by both rates of the amendments and was still present 10 years after the amendment. These data con®rm that agricultural soil abandonment leads to soil degradation and that the addition of urban waste could be a suitable technique with which to restore their quality
Keywords: dehydrogenase; hydrolases; organic matter; soil remediation

Soil microbial activity as a biomarker of degradation and remediation processes - Pascual, J. a; Garcia, C.; Hernandez, T.; Moreno, J. L.; Ros, M. (Soil Biology and Biochemistry, 2000)
Several organic matter fractions together with biological and biochemical parameters were measured in a range of intensively farmed soils in SE Spanish Mediterranean region, which had been abandoned (i.e. not used in agriculture) for different periods of time. These soils were compared with adjacent natural soils that had never been used for agriculture. There was a general decline of total organic carbon (TOC), extractable humic substances, water-soluble carbon (WSC) and carbohydrates, microbial biomass and respiration with the time elapsed since abandonment. There was also a decline in plant cover in the abandoned soils. When a degraded soil was amended with municipal solid waste at rates of 6.5 and 26 kg m 22 as a potential means of remediation, TOC, humic substances, WSC, microbial biomass and respiration rates signi®cantly increased but only at the higher rate of amendment. Plant cover was signi®cantly enhanced by both rates of the amendments and was still present 10 years after the amendment. These data con®rm that agricultural soil abandonment leads to soil degradation and that the addition of urban waste could be a suitable technique with which to restore their quality
Keywords: dehydrogenase; hydrolases; organic matter; soil remediation

MICROMORPHOLOGICAL, PHYSICAL, AND CHEMICAL CHARACTERISTICS OF LEACHING POORLY DRAINED FLAT SOILS OF CENTRAL SPAIN - Martin, A; MENDIZABAL, T; ZABALLOS, J P; BENAYAS, J (ARID SOIL RESEARCH AND REHABILITATION, 1995)
The eluviation process has been analyzed in horizons of Luvisols, Cambisols, and Acrisols on rana surfaces and in one Luvisol from the uppermost terraces of the Henares River. The soils are located in the supra- and meso-Mediterranean, dry and subhumid bioclimatic areas. Some now have vegetation of Quercus rotundifolia Lam. and Quercus pyrenaicae Willd. in serial stages, while others are used for cereal crops. The most indicative morphological variables of the eluviation process and their interrelationship with laboratory variables were studied (microstructure, texture, porosity, organic matter, and soluble salts). The E horizons have a loss of micromass in the thin section that coincides with a reduction in chlorides, sulfates, and electrical conductivity of the extract, as well as a very low ratio of Ca/Al water-soluble elements. Leaching is occasionally not shown in the granulometric analyses, but the transfer of matter due to biological activity and/or soil management is observed in the thin soil section. The Na+/Ca ratio greater than or equal to 1 matches a less stable microstructure, with a predominance of planar voids over vughs and channels. Sail use must be considered in the interpretation of this ratio. The eluviation horizons not described morphologically as such, namely Ap, Au, and Bw horizons in the rana formations and Au2, AB, and Bt1 horizons on the terrace, are always located in the upper 40 cm of soils that are used by plants. These are distinguished from the E horizons in their greater retention of available water and, depending on the eluviation intensity, a macroporosity higher than textural porosity.
Author
Keywords: micromorphology; organic matter; Porosity; soil leaching; soluble salts; transfere of matter